Estudantes indígenas no curso de Pedagogia EaD UFMT : percursos e processos de formação - Lima, Maria Moura (2020)
The present work is the result of a Master's research under the Graduate Program in Education, of the Federal University of Mato Grosso in the line of Research Social Movements, Political and Popular Education and aims to understand the paths and processes of formation of indigenous students of the A'uwư uptabi ethnic group (Xavante) in the Undergraduate Course in Pedagogy EaD/UAB/UFMT/IE reflecting on the difficulties, appropriations and inventions with the use of language and digital technologies. This intention of research brings in its bulge two questions that guide this work: what’s are the difficulties faced by indigenous students in the Pedagogy Degree course of EaD/UAB/UFMT/IE and what contributions can they offer with their ethnic education. The theoretical basis for this work permeates Freire’s educational ideas and conceptions (1987), FLEURI (1991), SANTOS (2018), WALSH (2001), GEERTZ (1997, 2008) and others who helped us during the research. The methodological path is qualitative with development of bibliographic research, documentary, as well as field study, understanding the Virtual Learning Environment (VLA) like this field of study, in the sense of direct contact with these students for informal conversations, interviews and all this through the use of digital media. The latter supported in interviews, semi-structured questionnaire, informal conversations and the observation of the experiences of the daily life of students in the virtual space (MINAYO, 1994, 2001, 2012, 2013). After data collection, the transcripts of the interviews and questionnaires were performed and, later, the organization and analysis of the collected material, followed by the interpretation of the results (GIL, 1994, 2002). The techniques of Participatory Rapid Diagnosis - DRP (WHITESIDE, 1994), which is a tool that allows the collection of information and knowledge of the reality of the community or institutions, from the point of view of its members, were also used. The students' cutout was by ethnicity A'uwư uptabi (Xavante) as a way of worrying the demands of the course. Its communities are located in the Brazilian Central Plateau, between the Mortes River and the trainers of the Xingu River, located east of the State of Mato Grosso in two poles and three municipalities: Água Boa, Canarana and Ribeirão Cascalheira. Thus, the study sought constant readings, observations in the AVA interfaces and the available and possible tools of communication with students, academic advisors and interviews with them and coordinators of the course under study. Thus, the contribution of the research is to clarify this doubt about the hypotheses of the difficulties that indigenous students A'uwư uptabi (Xavante) have been having with the use of language and digital technologies during the course cited, making it a possible space of build paths towards differentiated education to meet cultural, linguistic and that respects the education of their own teaching and learning processes of this ethnicity.